Hemoclot Thrombin Inhibitor Assay and Expected Peak-Trough Levels of Dabigatran: A Multicenter Study - Liu, Zhiyan; Mu, Guangyan; Xie, Qiufen; Zhang, Hanxu; Jiang, Jie; Xiang, Qian; Cui, Yimin (Frontiers in Cardiovascular Medicine, 2022)
Purpose Dabigatran concentrations monitoring are gaining importance of special situations, but limited data is available for the expected peak and trough levels. The Hemoclot Thrombin Inhibitor (HTI) is dabigatran-calibrated quantitative determination of dabigatran concentration. This study aims to validate HTI assay as the quantification choice of dabigatran, and providing the expected peak and trough levels. Methods This is a multi-center methodology validate study, including seven hospitals from Beijing, Shanghai, Henan, Hunan, Chongqing, and Fujian. We retrospectively analyzed plasma samples taken from 118 healthy subjects and 183 patients receiving dabigatran. Dabigatran concentrations were measured with HTI assay and high-performance liquid chromatography-tandem mass spectrometry (HPLC-MS/MS). Linear regression, Spearman correlation and Bland-Altman analysis were used in this study. Results The mean concentration ratio of HPLC-MS/MS and HTI assays was 1.03 and 0.98 at 2h and 12h, and the acceptance ranges for both the ratio limit as well as the limit of agreement were met, suggesting good agreement between the HTI-derived plasma concentrations and HPLC-MS/MS. The reference detection range of single dose dabigatran 150 mg in heathy subjects was 33-159 ng/mL. About 500 blood samples taken from 183 patients suggested that the expected peak and trough levels range of dabigatran 110 mg was about 95-196 and 36-92 ng/mL. Conclusions HTI assay can be a good quantitative detection method of dabigatran. Expected peak and trough levels provide a basis for the rational use of dabigatran, and provide important Asian population data for the update of the international clinical guidelines for hematological testing. The study has been registered on the Clinical Trials website with registration number of NCT03161496, registered on May 19, 2017.